Biosorption Potential of Phanerochaete chrysosporium for Arsenic, Cadmium, and Chromium Removal from Aqueous Solutions. Issue 12 (25th October 2018) - Rudakiya, Darshan M.; Iyer, Vignesh; Shah, Darsh; Gupte, Akshaya; Nath, Kaushik
Abstract: Efficient degradation of hazardous contaminants from contaminated water is the major challenge for researchers, wherein heavy metals are the prominent contaminants. Consequently, the assessment of multimetal removal is necessary using efficient biosorbant. In this work, the capability of Phanerochaete chrysosporium is evaluated for the individual and simultaneous removal of heavy metals. Individual and simultaneous removal of As, Cd, and Cr is optimized using response surface methodology based on the central composite design by changing the variables, i.e., pH, fungal biomass, and metal concentration. Optimization of the individual metal removal study reveals that fungus effectively absorbs As (29.95 mg L −1 ), Cd (18.1 mg L −1 ), and Cr (26.34 mg L −1 ) at 6.1, 5.64, and 4.15 of pH, respectively. Similarly, As (14.18 mg L −1 ), Cd (4.53 mg L −1 ), and Cr (9.28 mg L −1 ) are absorbed by fungal hyphae simultaneously within 1 h. Changes in the morphology of fungal hyphae are detected in metal absorbed samples as compared to the control hyphae. Interaction of metal‐absorbed fungal hyphae is analyzed using FTIR spectroscopy, revealing that the proteins, carbohydrates, and fatty acids present in the fungal cell are interacted with metals. The model white rot fungi used in the present study can be applied efficiently for the multimetal removal in effluent treatment plants. Abstract : Phanerochaete chrysosporium, a representative white rot fungus, is extensively utilized in environmental engineering for its favorable metal absorption ability. In the present study, this fungus is applied to the individual and simultaneous removal of arsenic, cadmium, and chromium, which is optimized using response surface methodology.